Manual removal versus spontaneous delivery of the placenta at caesarean section: a randomized controlled trial - Abdelfattah, Laila Ezzat; Bastawy, Abdullah Mohammed Abdullah; Fahmy, Mohamed Salah El Deen (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cesarean section (CS) is a life-saving surgery when certain complications occur during pregnancy and childbirth. The method of placental removing is one such procedure that can affect outcomes of cesarean delivery, such as the amount of bleeding during intraoperative and postoperative, the time of operation, the occurrence of postoperative endometritis, and may contribute to an increase or decrease in the incidence of CS. The objective of the study was to compare the manual removal of the placenta and spontaneous placental delivery at caesarean section. Methods: One hundred twenty sex consented to participate and divided randomly into two groups: Group A: included 63 pregnant women underwent elective caesarean section, the placental left in situ and the uterus massaged waiting spontaneous placental separation and Group B: included 63 pregnant women underwent elective caesarean section in which placenta was removed manually. Results: We found that women who had manual removal of the placenta lost significantly more blood than those who had spontaneous separation. A significant drop in hemoglobin was observed in manual separation group compared to spontaneous separation group. The median duration of placental delivery was shorter in manual separated group than spontaneously separated group. There was a statistically significant difference between both groups was found as regard the need for blood transfusion. There was a statistically significantly longer hospital stay with manual delivery of the placenta. Conclusions: Spontaneous separation of the placenta during cesarean section is more beneficial than manual separation.